2009
DOI: 10.1007/s00792-009-0244-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the bacterial populations of the highly alkaline saline soil of the former lake Texcoco (Mexico) following flooding

Abstract: Flooding an extreme alkaline-saline soil decreased alkalinity and salinity, which will change the bacterial populations. Bacterial 16S rDNA libraries were generated of three soils with different electrolytic conductivity (EC), i.e. soil with EC 1.7 dS m(-1) and pH 7.80 (LOW soil), with EC 56 dS m(-1) and pH 10.11 (MEDIUM soil) and with EC 159 dS m(-1) and pH 10.02 (HIGH soil), using universal bacterial oligonucleotide primers, and 463 clone 16S rDNA sequences were analyzed phylogenetically. Library proportions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 75 publications
6
53
0
1
Order By: Relevance
“…In one study, however, it was found that although Actinobacteria was represented in both medium and low saline soils, it was absent in extremely high saline soils (Valenzuela-Encinas et al 2009). The actinobacterial sequences were assigned to the subclasses Actinobacteridae, Acidimicrobidae, Nitriliruptoridae, and Rubrobacteridae.…”
Section: Bacteriamentioning
confidence: 96%
See 3 more Smart Citations
“…In one study, however, it was found that although Actinobacteria was represented in both medium and low saline soils, it was absent in extremely high saline soils (Valenzuela-Encinas et al 2009). The actinobacterial sequences were assigned to the subclasses Actinobacteridae, Acidimicrobidae, Nitriliruptoridae, and Rubrobacteridae.…”
Section: Bacteriamentioning
confidence: 96%
“…The dominant class within the Proteobacteria was Gammaproteobacteria, followed by Alphaproteobacteria and Deltaproteobacteria. In studies of soils from the former lake Texcoco, Valenzuela-Encinas et al (2009) showed that the dominant class of Proteobacteria in both high (158 dS m -1 ) and low (0.65 dS m -1 ) saline soils was Gammaproteobacteria, whereas in medium (56 dS m -1 ) saline soils the dominant class was Alphaproteobacteria. Furthermore, Deltaproteobacteria was present in both high and low saline soils, but absent in medium saline soils (Valenzuela-Encinas et al 2009).…”
Section: Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Percent soil moisture (⍜) was determined gravimetrically after oven drying. Soil pH was determined by combining 10 g soil with 10 ml deionized H 2 O. Nitrogen and carbon content were determined by using dry combustion on a Carlo-Erba C/N analyzer, and phosphorus (6,14), alpine hyper arid soils (9), hot desert (8,39,47), alpine tundra (37), Antarctic peninsula/coastal (6, 45), semiarid soils (1, 26, 32), prairies/grasslands (12, 41), pasture (22), crop agriculture (7,22,29,41,50), temperate forest (17,22,29,30,41), tropical forest (13), moist acidic tundra (5), and freshwater sediments (27,48 . Fibrobacter succinogenes was used as an outgroup.…”
mentioning
confidence: 99%